A Multicultural Approach in Islamic Education to Increase Tolerance - Mukarom, Zaenal; Renawati, Pande Wayan; Nurishlah, Laesti; Suhara, Djenal; Setiawan, Budi (International Education Trend Issues, 2024)
This study aims to explore the application of a multicultural approach in Islamic education as an effort to increase tolerance among students. In the midst of cultural, ethnic, and religious diversity in Indonesia, Islamic education is faced with the challenge of not only forming a religiously devout person, but also respecting differences and living in harmony in a pluralistic society. This study uses a qualitative method with a literature study approach. Data were collected through observation and analysis of documents, then analyzed qualitatively to identify patterns of application of multicultural values in the curriculum, teaching, and social interaction in schools. The results of the study show that a multicultural approach in Islamic education can strengthen the attitude of tolerance among students. The implementation of values such as respect for diversity, empathy, and cross-cultural dialogue in the teaching and learning process has been proven to be able to reduce prejudice and increase cooperation between groups. However, the success of this approach is highly dependent on teacher commitment and support from educational institutions and inclusive education policies. Therefore, it is recommended that Islamic educational institutions integrate a more systematic multicultural approach in their curriculum to create a more tolerant and harmonious educational environment.